Milking two or five times daily in the presence of a cow’s own nonsuckling calf fails to prolong postpartum anovulation - Lamb, G.C.; Thompson, K. E.; Heldt, J.S.; Löest, C.A.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three treatments were initiated at approximately 15 days after calving and continued for 4 weeks: 1) cows were suckled ad libitum by their calves (calf present [CP]); 2) calves were present but nonsuckling 24 hr/day and cows were milked twice daily (CR+2×M); 3) or same as CR+2×M but cows were milked five times daily (CR+5×M). Interval to the first postpartum ovulation was similar between CR+2×M and CR+5×M cows but about 2 weeks less than that in cows suckled ad libitum by their own calves. Cows in the CR+5×M treatment produced more milk than cows in the CR+2×M treatment, whereas only slight differences occurred in the percentages of milk fat, protein, lactose, and solids-not-fat. Prior to initiation of treatments, CR+2× cows yielded more milk than either CR+5×M or CP cows, but by the end of 4 weeks of treatment, milk yields were similar among treatments. We conclude that mechanical milking either two or five times daily in the presence of a cow’s own nonsuckling calf fails to prolong postpartum anovulation to the extent of ad libitum suckling. However, increasing milking frequency to 5× daily enhanced milk yield.
Keywords: Beef; Cows; Milking; Suckling; Calf presence; Anestrus